2006
DOI: 10.1007/s00277-005-0073-1
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in the management of chronic immune thrombocytopenic purpura: an effective and safe therapeutic alternative in refractory patients

Abstract: Rituximab induces B-cell depletion; therefore, it has been used in the treatment of immune thrombocytopenic purpura (ITP). The aim of this retrospective study was to evaluate the effectiveness of rituximab in the treatment of 89 patients with chronic ITP refractory to several treatments. All the patients had platelet counts <30 x 10(9)/l. They had received a median of five (2-13) previous treatments, and 47 had undergone splenectomy. Rituximab was administered i.v. at 375 mg/m(2) in four weekly doses in 77 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 17 publications
4
21
1
2
Order By: Relevance
“…This result is similar to other literature data. In fact, it is comparable with that reported in 5 other studies [9,11,12,13,14], which reported rates of 52% (13/25 patients), 54% (31/57 patients), 55.1% (49/89 patients), 44% (15/35 patients) and 57% (215/376), respectively. However, our result is inferior to some other reported data.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…This result is similar to other literature data. In fact, it is comparable with that reported in 5 other studies [9,11,12,13,14], which reported rates of 52% (13/25 patients), 54% (31/57 patients), 55.1% (49/89 patients), 44% (15/35 patients) and 57% (215/376), respectively. However, our result is inferior to some other reported data.…”
Section: Discussionsupporting
confidence: 79%
“…Moreover, Patel et al [9] did not find any relationship between initial lymphocyte subset profiles and the duration of response. Some authors have reported that a shorter disease duration is associated with a higher response rate [12,13,17,25]. Results from Zaja et al [1] and Gudbrandsdottir et al [2] in newly diagnosed pITP patients corroborate the hypothesis that better long-term effects of rituximab can be achieved when the antibody is administered earlier in the course of the disease.…”
Section: Discussionsupporting
confidence: 76%
“…Numerous studies about rituximab treatment for patients with refractory ITP were reported. However, most of the published studies only enrolled a limited number of patients and many were case reports [3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 96%
“…Rituximab erreicht bei etwa 30% der chronischen ITP-Patienten langfristige - definiert als über 12 Monate anhaltende - Remissionen [48,67]. Die übliche Dosis liegt bei 375 mg/m 2 1 × pro Woche für 4 aufeinanderfolgende Wochen.…”
Section: Drittlinientherapie Nach Splenektomieunclassified